Climate Justice: Essential to the Church's Mission - DiLeo, Daniel R. (Journal of religion & society. Supplement, 2020)
This essay argues that climate justice understood as faithful, prudent action to address climate change is essential to the mission of the Catholic Church. The first section outlines Catholic ecclesiology, missiology, and theological ethics as a response to God who is love (1 John 4:8). The second section outlines post-conciliar missiological conceptualizations with focus on the controversy about “action on behalf of justice” surrounding the 1971 synod of bishops’ document Justicia in Mundo and subsequent preparations for the 1974 synod of bishops. The third section presents the causes and consequences of climate change and the fourth section argues that climate justice is essential to the church’s mission. Section four especially suggests how climate justice might be enacted by persons and communities through charitable works and social justice and emphasizes the need for both proclamation and spirituality. The fifth section highlights the importance of prudence to climate justice.